Strategies for Ratifying Marriage Agreements to Avoid Partnership Liabilities - Almaududi, Almaududi; Hijriya, Shafira (Sekolah Tinggi Hukum Bandung, 2023)
This research aims to analyze the regulations and strategies for validating marriage agreements. This normative juridical research prioritizes secondary data as primary, secondary, and tertiary legal materials. Data was collected through document and literature studies and then analyzed qualitatively using a statutory and historical approach. The research findings indicate that the development of marriage agreement regulation can be categorized into three phases: before the enactment of Marriage Law, after the enactment, and after the Constitutional Court Decision No. 69/PUU-XIX/2016. Moreover, regulation remains unclear and has not been followed with legislation, giving rise to